Frontispiz: Towards Understanding the Reactivity and Optical Properties of Organosilicon Sulfide Clusters. (12th January 2021) - Hanau, Katharina; Schwan, Sebastian; Schäfer, Moritz R.; Müller, Marius J.; Dues, Christof; Rinn, Niklas; Sanna, Simone; Chatterjee, Sangam; Mollenhauer, Doreen; Dehnen, Stefanie
Abstract : Clusterchemie . Im Forschungsartikel auf S. 1196 berichten Simone Sanna, Sangam Chatterjee, Doreen Mollenhauer, Stefanie Dehnen et al. über Untersuchungen der weitgehend unerforschten Siliciumchalkogenid‐Cluster [(RSi)4 S6 ] und deren Reaktion mit [AuCl(PPh3 )].